Relasi Bahasa Dan Dialek: Studi Teoretis Terhadap Identitas, Variasi Dan Perubahan Bahasa - Rahmatika, Arum; Nandang, Ade (STIQ Amuntai, 2025)
This article explores the complex relationship between language and dialect from theoretical and sociolinguistic perspectives, focusing on three main dimensions: linguistic identity, socio-geographical variation, and the role of dialects in language change. The study argues that dialects are not merely informal variants of standardized language, but authentic expressions of social and cultural identity, as well as active agents in linguistic dynamics. Through a literature-based analysis, this paper highlights how dialects serve as markers of group solidarity, legitimate forms of linguistic variation, and sources of innovation in the evolution of language. However, dialects are often marginalized due to the dominance of standardized language, institutionalized through formal education and national language policies. The critical analysis in this article underscores the importance of recognizing dialects within educational systems and public policy as part of preserving linguistic diversity. The study recommends a more inclusive approach to language planning and multilingual education as essential strategies toward linguistic justice and the empowerment of local identities.